Performance of ASN Nurses during the Covid-19 Pandemic in terms of Self-Efficacy, Altruism, and Interpersonal Communication - Rokim, Mohammad; Sari, Erita Yuliasesti Diah; Aulia, Aulia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Nurses are at the forefront of overcoming the covid-19 pandemic, so nurses are required to have maximum performance, but in fact performance problems are found in nurses such as feeling unsure about overcoming the pandemic, fatigue, and decreased teamwork due to lack of health workers. This study aims to examine the effect of self-efficacy, altruism and interpersonal communication on the performance of ASN nurses during the Covid-19 pandemic. The subjects in this study were ASN nurses at Yogyakarta Hospital. Data collection uses employee performance appraisal (PKP) through the e-PKP system, self-efficacy scale, altruism scale and interpersonal communication scale. The collected data will then be analyzed using multiple linear regression techniques. The results showed that simultaneously self-efficacy, altruism and interpersonal communication have an influence on employee performance. Subsequent results show that there is no effect of self-efficacy on nurse performance, on the other hand there is an influence of altruism on nurse performance, and there is an influence of interpersonal communication on nurse performance. This research has implications for the importance of attention and increasing altruism and interpersonal communication to encourage nurse performance. Perawat merupakan garda terdepan untuk mengatasi pandemi covid-19 sehingga para perawat dituntut memiliki kinerja yang maksimal, tetapi pada faktanya permasalah kinerja ditemukan pada perawat seperti merasa tidak yakin untuk mengatasi pandemi, kelelahan, dan kerjasama tim menurun karena tenaga kesehatan yang kurang. Penelitian ini bertujuan untuk menguji pengaruh efikasi diri, altruisme dan komunikasi interpersonal dengan kinerja perawat ASN pada masa pandemi Covid-19. Subjek dalam penelitian ini adalah perawat ASN di RSUD Yogyakarta. Pengumpulan data menggunakan penilaian kinerja pegawai (PKP) melalui sistem e-PKP, skala efikasi diri, skala altruisme dan skala komunikasi Interpersonal. Data yang terkumpul selanjutnya akan dianalisis menggunakan teknik regresi linier berganda. Hasil penelitian menunjukkan bahwa secara simultan efikasi diri, altruisme dan komunikasi interpersonal memiliki pengaruh terhadap kinerja pegawai. Hasil berikutnya menunjukkan tidak ada pengaruh antara efikasi diri terhadap kinerja perawat, di sisi lain terdapat pengaruh altruisme terhadap kinerja perawat, dan terdapat pengaruh komunikasi interpersonal terhadap kinerja perawat. Penelitian ini berimplikasi pada pentingnya perhatian dan peningkatan altruisme dan komunikasi interpersonal untuk mendorong kinerja perawat.